1999
DOI: 10.1016/s0896-6273(00)81041-7
|View full text |Cite
|
Sign up to set email alerts
|

Orexin Synthesis and Response in the Gut

Abstract: Orexin (hypocretin) appears to play a role in the regulation of energy balances. Previous reports have indicated that orexin-containing neurons are found only in the lateral hypothalamic (LH) area. We show that a subset of neurons in the gut which also express leptin receptors display orexin-like immunoreactivity and express functional orexin receptors. Orexin excites secretomotor neurons in the guinea pig submucosal plexus and increases motility. Moreover, fasting upregulates the phosphorylated form of cAMP r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
242
0
31

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 290 publications
(290 citation statements)
references
References 43 publications
17
242
0
31
Order By: Relevance
“…7. Previous studies have demonstrated that OXR1 is clearly expressed in pancreatic islets and beta cells of pigs, rats and mice [9][10][11]. Here, we showed that OXA influenced insulin secretion in pancreatic islets through OXR1, but not OXR2.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…7. Previous studies have demonstrated that OXR1 is clearly expressed in pancreatic islets and beta cells of pigs, rats and mice [9][10][11]. Here, we showed that OXA influenced insulin secretion in pancreatic islets through OXR1, but not OXR2.…”
Section: Discussionsupporting
confidence: 48%
“…OXRs have been demonstrated not only in central neurons but also in some peripheral endocrine cells. Recent studies have demonstrated that OXR1 is expressed in the pancreatic alpha and beta cells of pigs, rats and mice [9][10][11] and in human and rat adipocytes [12,13]. Therefore, it is likely that orexins contribute to important endocrine functions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that orexins and their receptors are expressed in the NE cellular population of the digestive mucosa, where they play a role in the regulation of gut motility, blood flow, and epithelial secretion (Kirchgessner and Liu, 1999;Ehrström et al, 2005). In this study, the expression of oxA and of its highly specific receptor ox1R in the vestibular glands of the cattle genital tract was assessed.…”
Section: Discussionmentioning
confidence: 97%
“…The coexistence of 5-HT and oxA has been demonstrated in other organs of the mammalian body (Muraki et al, 2004;Wang et al, 2005;Tao et al, 2006). The human bowel contains NE cells costoring 5-HT and oxA whose secretion could stimulate both intrinsic and extrinsic primary afferent neurons (Kirchgessner and Liu, 1999). The peptide oxA has recently been found in NE cells of the cattle urethra (Russo et al, 2008), where 5-HT is widespread diffused.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation